PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN BUDAYA ORGANISASI TERHADAP PERILAKU ETIS AUDITOR PADA KAP - Wiwied Widyastuti; Unti Ludigdo (Universitas Brawijaya, 2010)
The issue of ethical behavior in Public Accountant Firms has received much attention in recent years. This research combines individual factors which includes emotional quotient, spiritual quotient and external factors as well as organization culture to predict and explain the auditors ethical behavior in Public Accountant Firms. The use of questionnaire instrument is adapted from Goleman (2005), Zohar & Marshall (2002), Robbins (2006), Arens, Loebbecke (1986). Population in this research is 49 auditors in East Java, as listed in the Directory of Public Accountant 2009. The results, which are based on multiple regression analysis, indicate that emotional quotient, spiritual quotient and organization culture increase auditors ethical behavior by 53,8%, while the remainder 46,2% is explained by other variables out of this model. Based on t analysis, spiritual quotient and organization culture have significant impacts on auditors’ ethical behavior. On the other hand, emotional quotient does not have significant effect on auditors’ ethical behavior. Future research is expected to extend area coverage, and use additional instrument to gain better insight for auditors’ ethical behavior. This research proposes that auditors’ ethical behavior could be improved so that audit profession could fulfill the ‘pillars of integrity’.